Content Based Image Retrivel on Non-Parametric Statistical Tests of Hypothesis - Selvaraj, S; Seetharaman, K (International Journal of Computer Sciences and Engineering, 2019)
The field of image processing is addressed significantly by the role of CBIR. Peculiar query is the main feature on which the image retrieval of content based problems is dependent. Relevant information is required for the submission of sketches or drawing and similar type of features. Many algorithms are used for the extraction of features which are related to similar nature. The process can be optimized by the use of feedback from the retrieval step. Analysis of color and shape can be done by the visual contents of image. Here neural network, Relevance feedback techniques based on image retrieval are discussed.